Orbit Transfers to Lower Altitude Orbits Using Aerobraking - Woo, Byoungsam; Coverstone, Victoria L. (The Journal of the astronautical sciences, 2003)
A strategy to obtain a temporary low altitude orbit (150 ~ 200 km at periapse) from a nominal higher altitude circular orbit using aerobraking is developed. The mission objective is to minimize propellant consumption subject to an upper bound on transfer time. The results are somewhat intuitive and show that the total delta-V is minimized when the orbital velocity of the satellite at the periapse on the transfer orbit is identical to the periapse velocity of the lower altitude mission orbit. Additionally, the general relation between transfer angle and the velocity at periapse on the transfer orbit is formed from numerical simulations. The developed strategy is employed for test cases of a low Earth orbit remote sensing satellite and a Mars mission. In each case, a linear relation of the transfer angle and the velocity at periapse on the transfer orbit is generated. A staircase-pattern relation between the transfer angle that minimizes total delta-V and the desired apoapse altitude of lower altitude mission orbit is generated for both Earth and Mars test cases.